Corrosion analysis - Dornbusch, Michael (CRC Press, Taylor and Francis Group, CRC Press is an imprint of the Taylor and Francis Group, an informa business, 2019)
"The book gives an overview on all relevant electrochemical and spectroscopic methods used in corrosion research. In addition to helping the reader choose the accurate method for a particular corrosion aspect, the various methods are correlated with industrial test methods for both the corrosion on metals (steel, zinc coated steel and aluminum) and the corrosion on coated metals (organic coatings and pre-treatments)"--